Persepsi Wisatawan Asing Terhadap Daya Tarik Pariwisata Di Wilayah Perbatasan Indonesia-Malaysia - Ersa Tri Fitriasari (Jurnal Good Governance, 2020)
This study aims to determine the perception of foreign tourists on vacation in IndonesiaMalaysia border region. The acceleration of development in border region is followed by the strategic steps in increasing the tourists through the management of the use of natural resources and human resources as a reflection of the frontline of the Republic of Indonesia. With the attraction of tourism can open investment opportunities, job vacancy for the poor local residents, open isolation with improved infrastructure. With Law No. 6 of 2014 regarding to the Village Autonomy in handling and managing existing natural resources and the development of village-owned enterprises as an effort to increase the community income and to handling the community services problems in the Malaysian border region as well as being a regional innovation within the framework of autonomy area. The results of the study using a qualitative approach as the main approach and quantitative approach as a supporter can be concluded that the results of the cross tabulation analysis test informants' perceptions that the distortion of tourism in the border region attracts foreign tourists with natural potential that can be used as a source of regional income. In-depth interview results show that the potential of border natural resources is exploited and tourism investment opportunities are opened by integrating the cultural, economic and environmental sectors by prioritizing the principle of inter-sectoral integration and village independence by optimizing the villages in the border region.Keywords: Perception, Tourism, Attraction, Border Areas